Correlation Analysis of the Number of Births Assisted by Health Workers and the Reduction in Maternal Mortality in Bogor Regency from 2003 to 2021 - Maulidia, Miftakul Fira; Perdana, Lukman; Khodijah, Syarifah; Jumiati, Sri; Siregar, Kemal Nazzaaruddin (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2023)
Maternal Mortality (MMR) is a major concern worldwide. In 2020, an estimated 287,000 women died during pregnancy or childbirth worldwide (WHO, 2020). One way to reduce maternal mortality is by ensuring that pregnant women have access to adequate and quality health services. This study aims to determine the correlation between the number of births assisted by health workers and the reduction in maternal mortality. This research is analytical with a quantitative approach using a dataset from the Bogor Regency health profile from 2003 to 2021. The results of the 2003-2021 data analysis using SPSS showed a negative correlation with a value of 0.57. The greater the number of births assisted by health workers, the lower the number of maternal deaths. Further analysis is needed using data on maternal health service coverage such as deliveries in health care facilities, handling of obstetric complications, Antenatal Care (ANC) coverage and iron supplementation tablet programs to increase the accuracy of research results and see a stronger relationship between maternal health services and the reduction in the number of maternal deaths.